Management A Legal Protection Women's Involvement In Narcotics Distribution With A Criminological Perspective - Suci Ramadani (Sean Institute, 2022)
One of the modus operandi in drug trafficking is to make women drug dealers. The narcotics business is getting out of control because manufacturers and big dealers use women as dealers. In almost all countries, The main cause of women's involvement in the global chain of drug trafficking is poverty. Poverty not only marginalizes women from various walks of life but also increasingly drags women into crime. The problem in this research is how to regulate narcotics dealers according to Indonesian law, what factors cause women to be involved in narcotics trafficking in terms of criminology and what efforts and obstacles need to be made to overcome women's involvement in narcotics trafficking. The purpose of this research is to examine the problems discussed. The type of research used is empirical research, namely in answering are problems, a legal perspective is used based on applicable legal regulations, to be further linked to the reality on the ground relating to the issues to be discussed. carried out field data collection techniques for the Langkat Police by conducting interviews with investigators and suspects in cases of women's involvement in drug trafficking.. Efforts and obstacles need to be made to overcome the involvement of women in drug trafficking that most women who are involved in drug trafficking are those who are divorced from their husbands or do not have a job, so to make ends meet they sell narcotics. Efforts have been made to increase the skills of housewives, especially those with single-parent status.